Utilization of the Quizizz Application as a Thematic Learning Evaluation Tool in Islamic Religious Education - Desti Meliana Ramandhani; Wantini; Halimatus Sadiah; Nurjannah Boru Hasibuan (al-Afkar, Journal For Islamic Studies, 2024)
Good and advanced education really requires increased learning activities and quality evaluation. In order to create a quality learning evaluation tool, there needs to be a connection between learning material and the use of technology. One technology that can be applied in carrying out learning evaluation activities is by utilizing an evaluation tool in the form of Quizizz. This research aims to determine learning evaluation tools and the use of the Quizizz application in thematic learning in Islamic Religious Education. This research uses a research method in the form of library research, with a qualitative approach. Meanwhile, analyzing the data uses the content analysis method. The content analysis method is to examine the contents of the book which will ultimately form a conclusion. The procedures carried out are: 1) Collect data sources such as journals and books related to thematic learning evaluation tools. 2) Sort and analyze the information that has been obtained. 3) After the data is collected, the researcher then analyzes the data so that a conclusion is drawn. The results of the research show that 1) Learning evaluation tools can be divided into two, namely tests and non-tests, 2) Evaluation tools using applications make students interested in learning activities and educators feel the benefits, namely in evaluating students more efficiently, increasing learning resources. for students and foster students' enthusiasm and enthusiasm in completing assignments, 3) The use of evaluation tools in thematic learning through Quizizz which accommodates learning needs aims to increase students' understanding and skills to achieve quality learning goals.